2011
DOI: 10.1111/j.1600-0536.2011.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt release from implants and consumer items and characteristics of cobalt sensitized patients with dermatitis

Abstract: It is often difficult to interpret the relevance of a positive patch test reaction to cobalt, and there is a need for further studies to determine sources of cobalt exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 48 publications
2
40
0
3
Order By: Relevance
“…Of the randomly selected sample of 50 new mobile phones for sale, no cobalt release was detected. 39 Interestingly, there have been four cases of patients with cell phone dermatitis deemed to have both nickel and cobalt sensitivity on patch testing, whose dermatitis improved with reduced cellular phone contact, however, the cellular phones were not tested for cobalt. 23,24 Given the rise in nickel and cobalt sensitization and reports of cell phone dermatitis in the literature, our aim was to investigate whether nickel or cobalt was present in top selling cellular phone models in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the randomly selected sample of 50 new mobile phones for sale, no cobalt release was detected. 39 Interestingly, there have been four cases of patients with cell phone dermatitis deemed to have both nickel and cobalt sensitivity on patch testing, whose dermatitis improved with reduced cellular phone contact, however, the cellular phones were not tested for cobalt. 23,24 Given the rise in nickel and cobalt sensitization and reports of cell phone dermatitis in the literature, our aim was to investigate whether nickel or cobalt was present in top selling cellular phone models in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…38 Historically, isolated cobalt allergy is seen in metal workers, brick layers, and pottery workers through occupational exposure. 39 However, a study conducted in the United States from 2001 to 2004 revealed that 12% of children with dermatitis had a relevant cobalt allergy. 40 Although a decrease in nickel sensitization was seen after the implementation of regulations in Europe, the prevalence of cobalt allergy remained the same.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Bir çalışmada, 50 telefonda kobalt içeriği araş-tırılmış, pozitif reaksiyona rastlanmamıştır. 30 Aquino ve ark.nın yaptığı çalışmada, 72 adet yedi farklı markanın telefonlarında kamera, tuşlar, metal logo, yan paneller ve hoparlör olmak üzere beş yer nikel ve kobalt içeriği açısından incelenmiştir. Yetmiş iki telefonun 24 tanesinde nikel, 10 tanesinde ise kobalt saptanmıştır.…”
Section: Cep Telefonlari Ve Akilli Telefonlara Bağli Geli̇şen Dermatozlarunclassified
“…Sarı olan reaktanın pembe renge dönmesi pozitif olarak değerlendirilmiştir. 30,31 Telefon dermatiti olup nikel ve kobalta karşı pozitif deri yama testi saptanan olgular bildirilmiş, ancak telefonlar kobalt açısından test edilmemiş-tir. 32,33 K Kr ro om m: : Nikel dermatiti kadar sık olmamasına rağmen preauriküler lokalizasyonda dermatit tablosu olup kroma karşı pozitif deri yama testi saptanan olgular bildirilmiştir.…”
Section: Cep Telefonlari Ve Akilli Telefonlara Bağli Geli̇şen Dermatozlarunclassified